Overall activity of Research and Development (R&D) division of BRAC Bank Ltd. - Rakhi, Rezoana Tasmin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.